Country-by-country reporting: Tension between transparency and tax planning - Maria Theresia Evers; Ina Meier; Christoph Spengel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
Aggressive tax planning efforts of highly profitable multinational companies (Base Erosion and Profit Shifting (BEPS)) have become the subject of intense public debate in recent years. As a response, several international initiatives and parties have called for more transparency in financial reporting, especially by means of a Country-by-Country Reporting (CbCR). In line with that, the OECD and the European Commission have recently presented proposals for a comprehensive disclosure of country-specific tax-related information for companies in all industry sectors. In our paper, we demonstrate that neither consolidated or individual financial statements nor other existing data sources seem to be an appropriate basis for providing such country-specific information. Instead, it would be necessary to define detailed and harmonized definitions and regulations to ensure comparability. The discussion on benefits and costs of a CbCR reveals that benefits (at least partially) lack a theoretical foundation and, overall, do not seem to outweigh associated costs. This holds true, in particular, since current tax planning activities are mainly based on the legal exploitation of gaps and loopholes in national and international tax law. Instead, we argue that tax legislators should limit profit shifting by enforcing tax rules and by closing gaps in tax law. In particular, we call for more tightened and standardized transfer pricing regulations and thin-cap rules to be adopted at an international level.
Keywords: H20; H26; F23; K34; M41; 330; tax avoidance; profit shifting; multinational firms; tax reform; tax reporting; country-by-country reporting; international transfer pricing